APPLICATION OF K-MEANS METHOD IN THE SPREAD OF POSITIVE CASES OF COVID-19 IN SALATIGA CITY - Gladis Tri Enggiel; Hindriyanto Dwi Purnomo (Informatika, Universitas Jenderal Soedirman, 2022)
Covid-19 is an infectious disease caused by SARS-CoV-2. It was discovered in Wuhan, China. It has been spread in every countries, especially in Indonesia. It has spreading all districts/cities in every province, one of it is City of Salatiga. This research used to determine the grouping of the spread of Covid-19 positive cases in each